Annual review of comparative and international education 2014 - Wiseman, Alexander W., 1968-; Anderson, Emily (Bingley, U.K. : Emerald, 2014)
The goal of the ARCIE volume is to examine current perspectives and future directions for the field using several essays as a context for discussion and analysis. Contributed Volume chapters begin by addressing the questions and themes discussed in these essays which will include: the use of new conceptual or methodological frameworks; the role of CIE in teacher education and higher education; the emergence of new area studies, and diversification of the field to include human rights, multicultural and social education, environmental education, education for sustainable development, arts education, and special education, among others. The format of ARCIE pieces entails an analytic overview of published work in the field, noting key issues and future directions. It provides an important and well-cited international forum for the discussion of matters of comparative and international education theory, policy and practice.
Introduction to the annual review : the reciprocal effects of teacher education on comparative and international education / Alexander W. Wiseman, Emily Anderson -- Trends and issues in the teaching of comparative education / Patricia K. Kubow, Allison H. Blosser -- Beyond pure forms : appraising the role of indigenous knowledge in teacher training / Trey Menefee, Tutaleni I. Asino -- Challenges and opportunities in incorporating comparative research into contemporary teacher education / Bruce Collet -- Information and communication technology for development in the field of comparative and international education / Jayson W. Richardson, Jeffrey Lee -- Inclusive education for all as special interest within the comparative and international education research community / Florian Kiuppis, Susan Peters -- Teacher education and professional development in global mathematics / Deepa Srikantaiah, Wendi Ralaingita -- Comparative and international education implications for the policy and practice of teacher education and the teaching profession / Chanita Rukspollmuang -- Perspectives from Africa : comparative education relevant research and teacher education / Lillian Katono Butungi Niwagaba , Christine M. Okurut-Ibore -- Reflections on comparative and international education, teacher education, and the Middle East / Carine Allaf -- Comparative perspectives on teacher education in South Asia / Radhika Iyengar, Matthew A. Witenstein, Erik Byker -- The influence of comparative and international education research on policymaking, teacher education and professional development in Greece / Dimitris Mattheou -- Conceptualizing teacher education in comparative and international context / John Weidman, W. James Jacob, Daniel Casebeer -- The schooling effect on neurocognitive development : implications of a new scientific frontier for comparative education / Daniel Salinas, David P. Baker -- Reforming teacher education through localization-internationalization : analyzing the imperatives in Singapore / Rita Zamzamah Nazeer-Ikeda -- Teacher education in Anglophone West Africa : does policy match practice? / Kabba E. Colley -- Education policy, teacher education, and pedagogy : a case study of UNESCO / Anthony Cerqua, Clermont Gauthier, Martial Dembélé -- The role of teachers in quality education in Latin America and the Caribbean : exploring new forms of horizontal cooperation / Laura C. Engel, Michaela Reich, Adriana Vilela -- Current challenges and future trends for teacher training in southern Africa : a focused look at Botswana and Lesotho / Cheryl Hunter, Tsooane Molapo -- India's 'cascade' structure of teacher education : its past and its future prospects / Rohit Setty -- Teacher education in transition : a reform program in initial teacher education in Pakistan / Shawana Fazal, Muhammad Khan, Muhammad Majoka.
Includes index.
Print version record
Keywords: Education -- Comparative; Education -- General; Education; Society & social sciences; Comparative education; International education